Was Joachim of Fiore a Mystic? A Few Observations on the Apocalyptic Spirituality of the Calabrese Abbot - GRZESZCZAK, JAN (Filozofia Chrześcijańska, 2018)
The article attempts to examine the presence of mystical elements in the writings of the Calabrese exegete, Joachim of Fiore (circ. 1135-1202). The fi rst part constitutes an overview of 12th century characteristic elements of apocalyptic spirituality, as seen by Joachim. This spirituality is infl uenced by both personal refl ections of this author and his intensive studies as well as current events, especially the crisis in the Church and the crusaders’ movement, as well as spreading heresies in the West and the progressive expansion of Islam. The second part of the article analyzes two intuitions of mystical nature which Joachim of Fiore experienced during his stay at the Cistercian Casamari Abbey. He elaborates on them in his major writings – Expositio in Apocalypsim and Psalterium decem cordarum. The nature of these intuitions and their later infl uence on this author’s writings allow the conclusion that we are dealing here with an experience that is mystical in nature, which, in turn, opened before Joachim some interpretative horizons that had been previously inaccessible in matters concerning the understanding (intelligentia) of inspired Writings.